Pengkajian Pelaksanaan dan Pengembangan Kapasitas Pengolahan Limbah Padat Dan Limbah Cair Di Bandara Sultan Thaha-Jambi - Yuke Sri Rizki; Rosidin Syamsudin (Research and Development Agency of The Ministry of Transportation, 2014)
Assessment of the implementation and development of the processing capacity of solid waste and liquid waste in an airport provides an overview of wastewater treatment systems generated from airport operations. This study takes a case study at Sultan Taha Jambi as airports are managed by PT Angkasa Pura II (Persero) that each year the relative increase in the number of aircraft movements, passenger, baggage and cargo transport. This study uses qualitative descriptive method and forecasting. The results of the analysis in the form of recommendations and the action carried out by the organizers of the airport is the expansion of the TPS (Disposal meantime), completing the construction of the WWTP (Waste Water Treatment Plant), and to separate waste into organic and non-organic at polling locations.Pengkajian tentang pelaksanaan dan pengembangan kapasitas pengolahan limbah padat dan limbah cair di bandar udara memberikan gambaran tentang sistem pengolahan limbah yang dihasilkan dari pengoperasian bandar udara.Pengkajian ini mengambil studi kasus di Bandara Sultan Thaha-Jambi sebagai bandar udara yang dikelola PT Angkasa Pura II (Persero) yang setiap tahun relatif mengalami peningkatan dalam jumlah pergerakan pesawat, penumpang, bagasi dan angkutan kargonya.Pengkajian ini menggunakan metode deskriptif kualitatif dan peramalan.Hasil analisis berupa rekomendasi dan program aksi yang dilaksanakan oleh penyelenggara bandar udara yaitu perluasan TPS (Tempat Pembuangan Sementara), menyelesaikan pembangunan IPAL (Instalasi Pengolahan Air Limbah), dan melakukan pemisahan sampah menjadi sampah organik dan non-organik di lokasi TPS.